Enrichment of Boron Using Physical and Chemical Methods: A Review - Bulut, Gülay; Aydın, Şükriye Beste; Perek, Kudret Tahsin; Arslan, Fatma (Informa UK Limited, 2025)
As it is well known, Turkey holds 72% of the world’s boron reserves. Therefore, the country has accumulated significant expertise in the enrichment of boron minerals, both in industry and in R&D studies. Upgrading of B2O3 content of the boron minerals can be done with several concentration methods, namely physical concentration, flotation, thermal, and chemical processes. Physical separation methods such as washing, trommel-screening, hand-sorting, classification, and attrition scrubbing are applied after size reduction. In the application of these methods, the particle size is as important as the type of gangue minerals present and clay removal is recommended before enrichment. The purpose of this review article is to examine the boron enrichment methods performed on ores and tailings in laboratories and plants. It has been found that many methods were successfully used.